1993
DOI: 10.1042/bj2940153
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin (ETA) receptor number and calcium signalling are up-regulated by protein kinase C-β 1 overexpression

Abstract: To evaluate the role of protein kinase C (PKC) in regulation of cellular responsiveness to mitogens, we used rat 6 (R6) fibroblasts that stably overexpress the beta 1 isoenzyme of protein kinase C (PKC-beta 1). The potent vasoconstrictor and mitogen endothelin-1 (ET-1; 100 nM) was substantially more effective in stimulating InsP3 accumulation in PKC-beta 1-overexpressing fibroblasts (PKC3 cells) than in control fibroblasts lacking the PKC-beta 1 cDNA insert. PKC3 cells were found to express a 7-fold greater nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Besides, pp42 and pp44 forms of mitogen-activated protein kinase are also phosphorylated in residues of tyrosine, and this effect is reduced by pretreatment with PTX, whereas the mentioned tyrosine phosphorylation of focal adhesion kinase remained intact (24). On the other hand, rat-6 fibroblasts, overexpressing PKC-␤1, showed an increased calcium signaling in the presence of endothelin; in this case, an increase in the number of ET A receptors was detected (47). It is possible that GRKs could be activated by ET A receptors; however, GRKs are reported to phosphorylate only receptors in the agonist-occupied state; the participation of these kinases in the heterologous phosphorylation of ␣ 1b -ARs seems unlikely.…”
Section: Discussionmentioning
confidence: 92%
“…Besides, pp42 and pp44 forms of mitogen-activated protein kinase are also phosphorylated in residues of tyrosine, and this effect is reduced by pretreatment with PTX, whereas the mentioned tyrosine phosphorylation of focal adhesion kinase remained intact (24). On the other hand, rat-6 fibroblasts, overexpressing PKC-␤1, showed an increased calcium signaling in the presence of endothelin; in this case, an increase in the number of ET A receptors was detected (47). It is possible that GRKs could be activated by ET A receptors; however, GRKs are reported to phosphorylate only receptors in the agonist-occupied state; the participation of these kinases in the heterologous phosphorylation of ␣ 1b -ARs seems unlikely.…”
Section: Discussionmentioning
confidence: 92%
“…More importantly, the up-regulated expression of ET A receptors, but not ET B receptors, suggests that ET A receptors may be the therapeutic target for EPC dysfunction in salt-sensitive hypertension. It has been reported that protein kinase C (PKC) induces ET A receptors at a transcriptional level in rat fibroblasts 15 or in cardiac cells from DOCA-salt hypertensive 16 . However, whether these possibilities exist in EPCs remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism could be homologous down-regulation by increased local production of the ET peptide. This is unlikely since RMICs have not been shown to produce ET in vivo (28) (30)(31)(32)(33). This is also unlikely since H-7, a PKC inhibitor, was without effect on the reduction in ET receptors following incubation with 600 mOsm/kg urea.…”
Section: Discussionmentioning
confidence: 99%